Listeners' preference and the media's thematic focus on public issues: an exploration of agenda-setting as a two-way process (2013)
The mass media have the power to set public agenda. Public issues that receive emphasis by the media are the issues that are likely to receive prominence in public perception. However, it has been argued that there is a link between what the public expect to constitute news and what the media report as news to set public agenda. This assertion requires further empirical proof, especially in the Nigerian media context. Focusing on radio listeners and the news review programmes of selected radio stations in Oyo State, Nigeria, this study sought to establish the validity or otherwise of the forgoing contention. Premised on agenda-setting and newsworthiness theories, the study combined In-depth Interviews, Content Analysis and Survey as research methods. Findings show that a predominant segment (89.0%) of radio listeners perceived the intensity of media coverage of certain public issues as an indicator that such public issues must be significant: Issues such as politics (33.5%), sports (29.5%), and crises (11.3%) that audience preferred as news were the same issues that the radio stations accorded corresponding degree of emphasis in the news reviews-politics (35.4%). sports (17.0%), and crises (11.9%). Editorial personnel of the radio stations also affirmed that they gave priority to issues that would naturally interest the audience. The basic implication of these findings is that as the media set agenda for the public, the public also set agenda for the media.